2012
DOI: 10.2174/092986612802084465
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction Between Endostatin Short Peptide and VEGF Receptor 3

Abstract: Corneal angiogenesis and lymphangiogenesis are induced by vascular endothelial growth factors (VEGFs) signaling through its receptors VEGFR-1, -2, and -3. Endostatin is a peptide antagonist of these receptors that causes inhibition of bFGF-induced corneal angiogenesis and lymphangiogenesis. Here we show that binding of VEGF-C and endostatin to recombinant VEGFR-3 is competitive. Alignments of the primary amino acid sequences of VEGF-C and the C-terminal endostatin peptide (mEP: LEQKAASCHNSYIVLCIENSFMTSFSK) ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…VEGFR-3 (also known as flt-4), another receptor tyrosine kinase, is expressed primarily on lymphatic endothelial cell surfaces [103]. Endostatin competitively inhibits VEGF binding to VEGFR-3 in vitro [104]. Once bound, endostatin serves as an anti-lymphangiogenic factor by inhibiting VEGF-stimulated lymphatic endothelial cell proliferation and migration [104].…”
Section: Endostatin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGFR-3 (also known as flt-4), another receptor tyrosine kinase, is expressed primarily on lymphatic endothelial cell surfaces [103]. Endostatin competitively inhibits VEGF binding to VEGFR-3 in vitro [104]. Once bound, endostatin serves as an anti-lymphangiogenic factor by inhibiting VEGF-stimulated lymphatic endothelial cell proliferation and migration [104].…”
Section: Endostatin Receptorsmentioning
confidence: 99%
“…Endostatin competitively inhibits VEGF binding to VEGFR-3 in vitro [104]. Once bound, endostatin serves as an anti-lymphangiogenic factor by inhibiting VEGF-stimulated lymphatic endothelial cell proliferation and migration [104]. …”
Section: Endostatin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also one of few tissues in the body that is normally devoid of any vascular blood or lymphatic structures. Studies have identified multiple mechanisms, including the expression of anti-angiogenic factors, lack of pro-angiogenic factors, and expression of soluble VEGF receptors as underlying mechanisms for maintaining cornea avascularity [15]. However, many pathological conditions such as trauma, chemical injury, inflammation, and infection can break the balance of pro- and anti- angiogenic actions, resulting in hem-angiogenesis (HG; the development of new blood vessels) and lymph-angiogenesis (LG; the development of new lymphatic vessels) [69].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 It is important to keep in mind that the counterbalancing mechanism that regulates angiogenesis is the overproduction of angiogenic stimulators (VEGF) and the underproduction of angiogenic inhibitors (e.g., angiostatin, endostatin). 15,[39][40][41] Because this balance is so delicate, therapeutic alternatives targeting angiogenic inhibitors are as essential as those targeting angiogenic stimulators. In one study of angiogenic inhibitors, Zhang et al examined the effects of plasminogen kringle 5 (K5), a proteolytic fragment of plasminogen that functions as a potent angiogenic inhibitor by preventing the proliferation of endothelial cells.…”
Section: Anti-vegf Treatmentsmentioning
confidence: 99%